Patient and Provider Perception of Transurethral Resection of Bladder Tumor vs Chemoablation for Nonmuscle-invasive Bladder Cancer Treatment. Issue 1 (6th January 2023) - Parisse, Taylor; Reines, Katy; Basak, Ramsankar; Mueller, Dana; Teal, Randall; Vu, Maihan B.; Carda-Auten, Jessica; Stein, Kathryn; Giannone, Kara; Lipman, Robert; Smith, Angela B.
Abstract : Purpose: The aim of this mixed methods study was to investigate patient and provider perceptions of repeat transurethral resection of bladder tumors to improve counseling as new nonsurgical treatment modalities for nonmuscle-invasive bladder cancer emerge. Materials and Methods: Quantitative data were collected via a web-based survey through the Bladder Cancer Advocacy Network of patients with nonmuscle-invasive bladder cancer who had undergone at least 1 transurethral resection of bladder tumor. Bivariable and multivariable analyses were performed to evaluate associations of patient demographics and clinical variables with treatment preference. Qualitative data were collected with 60 in-depth telephone interviews with patients (n=40) and urologists (n=20) to understand experiences with bladder cancer and transurethral resection of bladder tumor. Telephone interviews were conducted by trained qualitative experts. Transcripts were imported into Dedoose to facilitate analysis. Results: Survey data of 352 patients showed 210 respondents (60%) preferred repeat transurethral resection of bladder tumor while 142 (40%) preferred intravesical chemoablation. Patients who preferred repeat transurethral resection of bladder tumor were more likely to prioritize initial treatment effectiveness (63%), whereas those who preferred chemoablation prioritized risk of recurrence (55%). Variables associated with a preference for intravesical chemoablation included U.S. residence (OR=2; 95% CI 1.1, 3.8), or if they expressed their reason for treatment preference as priority of recurrence risk over effectiveness (OR=14.6; 95% CI 7.4, 28.5). Predominant interview themes varied across participants, with patients but not urologists emphasizing the emotional toll of the procedure along with the need for improved counseling regarding recurrence, terminology, and cancer-related signs and symptoms. Conclusions: Differences exist in the way patients and urologists perceive repeat transurethral resection of bladder tumor for bladder cancer. Understanding transurethral resection of bladder tumor perception will aid in shared decision making as novel treatments emerge for nonmuscle-invasive bladder cancer.